Motor imagery involves predicting the sensory consequences of the imagined movement - Konstantina Kilteni (Nature Portfolio, 2018)
Forward models predict and attenuate the sensory feedback of voluntary movement yet their involvement in motor imagery has only been theorized. Here the authors show that motor imagery recruits forward models to elicit sensory attenuation to the same extent as real movements.